2019
DOI: 10.1097/md.0000000000015163
|View full text |Cite
|
Sign up to set email alerts
|

A safe percutaneous technique for the reduction of irreducible femoral neck fractures using ultrasound localization of the femoral vascular and nervous structures at the hip

Abstract: We present a safe percutaneous technique for the placement of Kirschner wires into the femoral head to assist in the reduction of irreducible femoral neck fractures using ultrasound to identify the vascular and nervous structures about the hip. From January 2011 to June 2014, a total of 36 patients (25 males and 11 females) were enrolled in this study. Patients were placed on a fracture reduction table for limb traction. After 3 unsuccessful reductions with limb traction, ultrasound-guided localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“… [9] Mahaisavariya et al reported on adult intramedullary nail fixations under ultrasound monitoring. [10] Yu et al have also reported similar findings, [11] but no studies on children have been reported.…”
Section: Discussionmentioning
confidence: 66%
“… [9] Mahaisavariya et al reported on adult intramedullary nail fixations under ultrasound monitoring. [10] Yu et al have also reported similar findings, [11] but no studies on children have been reported.…”
Section: Discussionmentioning
confidence: 66%
“…This is in accordance with our study, where 83.3% (5/6) of the patients with trans xion pin injuries recovered completely. We believe that in the future, high-risk patients, such as those with obesity, may warrant B-mode ultrasound-guided pin placement to reduce the development of complications, similar to the method used by Yu et al [18] for the reduction of femoral neck fractures.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of anatomic reduction of these fractures has led to multiple descriptions of surgical techniques to achieve the best possible reduction. [18][19][20] Yu et al 18 described a percutaneous reduction method using Kirschner wires as joysticks and ultrasonography for localization of important structures to prevent injury. This is a relatively limited series, however, with 36 patients and four postoperative complications (one planned total hip, one osteonecrosis, one screw migration, and one screw loosening).…”
Section: Approach and Reduction Techniquesmentioning
confidence: 99%